Essential oil of Lippia origanoides as an anesthetic for Piaractus mesopotamicus: implications for induction and recovery times, ventilatory frequency and blood responses after biometric management - R. G. S. Almeida; A. L. Ferreira; R. M. G. Acunha; N. S. Oliveira; N. Pompiani; K. K. C. Oliveira; D. C. Costa; F. C. M. Chaves; C. M. Campos (Brazilian Journal of Biology)
Abstract This study evaluated the use of the essential oil of Lippia origanoides (EOLO) as an anesthetic for juvenile pacu, Piaractus mesopotamicus. Two experiments were performed. In Experiment I, anesthetic induction and recovery times and ventilatory frequency (VF) were determined for fish (n= 48; 29.94 ± 6.69 g) exposed to different EOLO concentrations [0 (control - 4000 µL alcohol L-1), 25, 50, 100, 200 and 400 µL L-1]. From the responses obtained in Experiment I, the EOLO concentrations of Experiment II (n= 36; 29.25 ± 5.90 g) were determined, which evaluated the effects of 0 (control - 2000 µL alcohol L-1), 50 (outside recommended induction and recovery times) and 200 µL L-1 (within recommended induction and recovery times) by analyzing immunohematological and biochemical parameters at different collection times (1 h and 24 h post-induction). Fish survival was 100% in both experiments. The EOLO concentration of 25 µL L-1 was not able to induce deep anesthesia in the animals, while the concentration of 200 µL L-1 showed induction and recovery times within the range indicated for fish and was efficient at reducing VF during induction. No differences were observed in immunohematological and biochemical parameters among concentrations, but differences were observed in comparisons between collection times. Nonetheless, blood variables returned to levels considered normal for the species in approximately 24 hours. Therefore, an EOLO concentration of 200 µL L-1 can be considered safe for use prior to biometric management of P. mesopotamicus.